LOCATION INTEGRITY PROTECTION - HSU, Kang-Che; ZOU, Guang Tai; YE, Ting (2024)
Example embodiments of the present disclosure relate to an SBC, an STI-AS, an STI-VS, methods, apparatuses and a computer readable storage medium for location integrity protection. In some embodiments, the SBC receives, from a location provider, a first SIP message comprising location information; transmits, to an STI-AS, a signing request comprising the location information; receives, from the STI-AS, a signing response comprising identity information associated with the location information; and transmits, to a further device, a second SIP message based on the first SIP message and the identity information. As such, since the location information is signed by the STI-AS, the downstream network may validate the signed information for data integrity; therefore, the location information in a SIP message may be validated, to determine whether it has not been spoofed, mocked, or attacked. Selon des exemples de modes de réalisation, la présente invention concerne un SBC, un STI-AS, un STI-VS, des procédés, des appareils et un support de stockage lisible par ordinateur pour la protection d'intégrité de localisation. Selon certains modes de réalisation, le SBC reçoit, d'un fournisseur de localisation, un premier message SIP comprenant des informations de localisation ; transmet, à un STI-AS, une demande de signature comprenant les informations de localisation ; reçoit, du STI-AS, une réponse de signature comprenant des informations d'identité associées aux informations de localisation ; et transmet, à un autre dispositif, un second message SIP sur la base du premier message SIP et des informations d'identité. Ainsi, étant donné que les informations de localisation sont signées par le STI-AS, le réseau en aval peut valider les informations signées pour l'intégrité des données ; par conséquent, les informations de localisation figurant dans un message SIP peuvent être validées, pour déterminer si elles n'ont pas été usurpées, contrefaites ou attaquées.